The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/w11122553
|View full text |Cite
|
Sign up to set email alerts
|

Potential of A Trait-Based Approach in the Characterization of An N-Contaminated Alluvial Aquifer

Abstract: Groundwater communities residing in contaminated aquifers have been investigated mainly through taxonomy-based approaches (i.e., analyzing taxonomic richness and abundances) while ecological traits have been rarely considered. The aim of this study was to assess whether a trait analysis adds value to the traditional taxonomy-based biomonitoring in N-contaminated aquifers. To this end, we monitored 40 bores in the Vomano alluvial aquifer (VO_GWB, Italy) for two years. The aquifer is a nitrate vulnerable zone ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Based on what has been observed for the meiofauna of lotic environments, it is assumed that these traits are very diversified also for the meiofauna of lakes due to the disparate number of taxa living in lakes. The "life history" trait was mainly investigated concerning the age structures and sex ratio in Nematoda [50][51][52][53], although these two aspects have proved to be effective in describing the life histories of groundwater copepods as well [14,30]. Furthermore, the study of temperature-dependent life-history traits, such as development, reproduction, and population growth rates, can be successfully carried out for some species of Copepoda in the laboratory, using mesocosms [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on what has been observed for the meiofauna of lotic environments, it is assumed that these traits are very diversified also for the meiofauna of lakes due to the disparate number of taxa living in lakes. The "life history" trait was mainly investigated concerning the age structures and sex ratio in Nematoda [50][51][52][53], although these two aspects have proved to be effective in describing the life histories of groundwater copepods as well [14,30]. Furthermore, the study of temperature-dependent life-history traits, such as development, reproduction, and population growth rates, can be successfully carried out for some species of Copepoda in the laboratory, using mesocosms [54].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, "thermal preference" was intended as a physiological response trait related to the functional abilities of an organism, with a potential impact on fitness. To attribute the classes to the categories of response and effect traits, we followed the study of Moretti et al [10] and others trait-based studies carried out on the meiofauna of lakes [24], rivers [27,28], hyporheic zones of rivers [29] and groundwater [14,30]. Some of the fiftytwo keywords related to the above traits were composed of more than one word (for example: "raptorial feeders").…”
Section: Methodsmentioning
confidence: 99%
“…Nitrate contamination can, therefore, persist for years [14]. Di Lorenzo et al [15] analyzed the effects of long-term nitrate contamination on the groundwater fauna of an alluvial aquifer in central Italy. The study revealed that structural traits of the biological assemblages, such as the ratios of juveniles to adults and of males to females, as well as the relationships between abundances and biomasses, provide indicators of the alteration of the communities in a more efficient way than classical taxonomy-based analyses, which are focused on species richness and abundances only.…”
Section: Groundwatermentioning
confidence: 99%
“…Erős et al, 2009; Hoeinghaus et al, 2007; Várbíró et al, 2020), hyporheic zones (Descloux et al, 2014; Di Lorenzo, Fiasca, et al, 2021), lakes (Hébert et al, 2016) and wetlands (Van Bodegom et al, 2006). Except for a small number of recent papers, such as those by Di Lorenzo, Murolo, et al (2019), who compared functional traits of groundwater invertebrate fauna (stygofauna) in response to nitrate contamination in a porous aquifer, and those by Borko et al (2021) and Fišer et al (2019), who analysed morphological traits to test niche differentiation in subterranean amphipods, there has been little analysis of biological traits of groundwater organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Trait‐based approaches have the advantage of being able to indicate the mechanisms of biotic responses to environmental change, allow consistent descriptors or metrics across broad spatial scales that transcend taxonomic descriptions and distributions, and have less seasonal and interannual variability compared with traditional taxonomy‐based community metrics (van den Brink et al, 2011). With groundwater resources and ecosystems under immense pressure globally (Mammola, Cardoso, et al, 2019; Mammola, Piano, et al, 2019), traits may provide a sensitive and informative means to better understand these systems and assess ecological risk and change (Culp et al, 2011; Di Lorenzo, Murolo, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%